Other Research – Information Technology for Protected Individuals: A Survey of Current Status - Manouchehr Tabatabaei (Disability Studies Quarterly, 2002)
Information technology has greatly impacted the life of everyone in recent years. It is therefore important to be aware of current technology and know how it can improve functional participation in today's society that is better known as the "Information" Society. The purpose is to foster equality in using technology for everyone, able or disabled. Everyone should have equal access to technology and the presence of a disability should not preclude one from this benefit. The purpose of this article is to summarize important developments in computer technology for individuals experiencing disability and to provide a brief explanation of how they can be utilized to promote participation in society.